Thoracic outlet syndrome (TOS): A case report of a rare complication after Nuss procedure for pectus excavatum. Issue 36 (September 2018) - Zhang, Weiqiang; Pei, Yingxin; Liu, Keqiang; Tan, Jian; Ma, Jingbo; Zhao, Jing
Abstract: Rationale: The Nuss procedure has become a major alternative operation for patients with pectus excavatum (PE). Patient concerns: We report a case of 27-year-old man with PE who developed thoracic outlet syndrome (TOS) after the Nuss procedure. The patient showed clinical symptoms of brachial plexus compression. Diagnoses: Further evaluation demonstrated a narrowed space between the first rib and the anterior scalene muscle and compressing the brachial plexus and vessels. Interventions: Nerve nourishing medicine and rehabilitation exercising were taken to restore the muscle strength. Outcomes: Several months later, the clinical symptoms disappeared. Lessons: Medicine and rehabilitation exercising may benefit the functional recovery of impaired nerve in TOS in the early stage of TOS.